1998
DOI: 10.1002/ana.410440603
|View full text |Cite
|
Sign up to set email alerts
|

Imaging epileptogenic tubers in children with tuberous sclerosis complex usingα‐[11C]Methyl‐L‐tryptophan positron emission tomography

Abstract: Several reports have indicated that cortical resection is effective in alleviating intractable epilepsy in children with tuberous sclerosis complex (TSC). Because of the multitude of cortical lesions, however, identifying the epileptogenic tuber(s) is difficult and often requires invasive intracranial electroencephalographic (EEG) monitoring. As increased concentrations of serotonin and serotonin-immunoreactive processes have been reported in resected human epileptic cortex, we used alpha-[11C]methyl-L-tryptop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
129
0
8

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 249 publications
(139 citation statements)
references
References 40 publications
2
129
0
8
Order By: Relevance
“…Epileptogenic tubers have been found to have increased AMT uptake compared with surrounding cortex and nonepileptogenic tubers. 2,10 In an analysis of 17 patients selected for resection, AMT-PET studies were included in the preoperative evaluation, and 77% of the cortical tubers with increased AMT uptake were within the EEG-defined region. Of those patients with a single tuber that exhibited AMT uptake, the tuber was always within the electroencephalographic region of interest.…”
Section: Novel Methods For Preoperative Evaluation In Tscmentioning
confidence: 99%
“…Epileptogenic tubers have been found to have increased AMT uptake compared with surrounding cortex and nonepileptogenic tubers. 2,10 In an analysis of 17 patients selected for resection, AMT-PET studies were included in the preoperative evaluation, and 77% of the cortical tubers with increased AMT uptake were within the EEG-defined region. Of those patients with a single tuber that exhibited AMT uptake, the tuber was always within the electroencephalographic region of interest.…”
Section: Novel Methods For Preoperative Evaluation In Tscmentioning
confidence: 99%
“…Subsequent studies using AMT PET in children with tuberous sclerosis and epilepsy have shown focal accumulation of AMT in epileptogenic (but not in nonepileptogenic) tubers (Chugani et al, 1998a;Asano et al, 2000;Fedi et al, 2003); this accumulation is likely the result of epileptogenic tubers containing increased levels of quinolinic acid, which is a convulsant and neurotoxic metabolite of the kynurenine pathway (Chugani et al, 1998b;Chugani and Muzik, 2000). Subsequent studies in patients with intractable seizures of various etiologies, including malformations of cortical development, found that increased AMT was highly specific for epileptogenic cortical regions and is a useful method for presurgical evaluation of some patients with intractable epilepsy (Asano et al, 2000;Fedi et al, 2001;Juhász et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…11 We previously reported, in a relatively small number of patients with TSC, that a-[ 11 C]-methyl-Ltryptophan (AMT)-PET scanning may differentiate between epileptogenic tubers (high AMT uptake) and nonepileptogenic tubers (low AMT uptake) and that the location of high AMT uptake corresponds to the seizure focus on EEG. 6,12,13 …”
Section: Resultsmentioning
confidence: 99%
“…Our results are consistent with previous smaller studies demonstrating that epileptogenic tubers frequently show increased AMT uptake. 6,12,13,21 The incremental value of AMT-PET over standard investigations is illustrated by i) 10 of 17 patients (58%) with nonlateralizing ictal scalp EEG but lateralized increased AMT-PET uptake, and ii) 28 of 68 patients (41%) whose ictal EEG was lateralizing but nonlocalizing in whom AMT-PET provided localizing information to guide placement of intracranial electrodes. Our findings suggest that AMT-PET could provide additional lateralization/localization data to the standard modalities in the pre-epilepsy surgical evaluation of patients with TSC.…”
Section: Statistical Analysis Quantitative Values Are Expressed As Mmentioning
confidence: 99%
See 1 more Smart Citation